BAKSO SINTETIS BAKSO SINTETIS DARI CAMPURAN GLUTEN TEMPE DENGAN PENAMBAHAN TEPUNG TAPIOKA (Jurnal Teknologi Pangan, 2018)
BAKSO SINTETIS BAKSO SINTETIS DARI CAMPURAN GLUTEN TEMPE DENGAN PENAMBAHAN TEPUNG TAPIOKA